A retrospective analysis of frozen-thaw embryo transfer (FET) cycle outcomes at Tygerberg Academic Hospital. - Dikgang, Olebogeng Kumbilani (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMed)--Stellenbosch University, 2024.